Decisive Parameters for Backwater Effects Caused by Floating Debris Jams - Hartlieb, Arnd (Scientific Research, 2015)
The dimensional analysis of the backwater effect caused by debris jams results in the Froude number of the approach flow in the initial situation prior to debris jam formation and the debris density as decisive parameters. For the more precise detection of the influence of both parameters the results of different hydraulic model test series at the Laboratory of Hydraulic and Water Resources Engineering of the Technical University of Munich concerning debris jams at spillways as well as at racks for the retention of wooden debris were uniformly evaluated. On the one hand a significant increase of the backwater effect with a rising Froude number of the approach flow could be shown. This is in good correlation to recent test results for debris jams at retention racks at the Laboratory of Hydraulics, Hydrology and Glaciology of the Swiss Federal Institute of Technology Zurich. On the other hand a significant increase of the backwater effect could also be shown for a rising debris density. However, the test results also show that significantly different backwater effects can occur in different test runs with identical test conditions. These differences are a result of the randomness of debris jam development, and therefore, a more exact quantification of the dependence of the backwater effect on the Froude number of the approach flow and on the debris density is not considered useful for the present results.
Keywords: Hydraulic Engineering; Natural Hazards; Floating Debris Jams; Large-Scale Hydraulic Model Tests